Relationship between diet, body mass index and frequency of exercise per week on students' physical fitness levels - Deddy, Deddy Whinata (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2024)
This research has three purposes. The first purpose is to find out the relationship between diet and physical fitness. Secondly, it aims to find out the relationship between body mass index and physical fitness. And the last purpose is to find out the relationship between frequency of exercise per week and physical fitness, and finally to find out the relationship between diet and mass index. body and frequency of exercise per week on the physical fitness level of elementary school male students. The purpose of this study was to determine, the relationship between body mass index and physical fitness, and the relationship between exercise frequency per week, physical fitness and the relationship between diet, body mass index and exercise frequency per week on the level of physical fitness of male elementary school students. This study was conducted on elementary school children aged 5-12 years and this study has a target completion starting from preparation, data collection and data processing. In this study, the Nusantara Student Fitness Test (TKPN) tool was used to collect data on the level of physical fitness and diet and exercise frequency per week using a research questionnaire. The results of the data analysis can be presented as follows, the first result is a relationship between diet and physical fitness of male elementary school students after being known using the Pearson product moment correlation with a significance value of 0.000 which shows an effect of 19.9%. Second, there is a relationship between Body Mass Index and physical fitness in male elementary school students after being known using the Pearson product moment correlation with a significance value of 0.000 showing an effect of 5.5%. Third, there is a relationship between the frequency of exercise per week and the physical fitness of male elementary school students after being known using the Pearson product moment correlation with a significance value of 0.004 which shows an influence of 9.8%. Based on these results, it can be concluded that there is a positive correlation, which means that there is an influence between diet, body mass index and frequency of exercise per week on the physical fitness of male elementary school students